Anatomopathologic Study of Kidneys parasitized by Dioctophyme renale in Dogs - Sapin, Carolina da Fonseca; Silva-Mariano, Luísa Cerqueira; Piovesan, Andressa Dutra; Fernandes, Cristina Gevehr; Rappeti, Josaine Cristina da Silva; Braga, Fabrício de Vargas Arigony; Cavalcante, Guilherme Albuquerque; Rosenthal, Bruna Müller; Grecco, Fabiane Borelli (Acta Scientiae Veterinariae, 2017)
Background: Dioctophymiasis is a disease caused by the nematode Dioctophyme renale and is a relatively common condition in dogs. The parasite affects the kidney, especially the right, enters the kidney capsule and causes destruction and atrophy of the parenchyma. The lesion severity depends on the amount of parasites affecting the kidney, the duration of the infection, number of kidneys involved and concurrent occurrence of kidney disease. The disease’s clinical presentation may be asymptomatic or with nonspecific clinical signs. The diagnosis is based on ultrasound examination and the detection of eggs in urine, however, diagnosis is often reached only through necropsy or histopathology. This study aimed to analyze the dog kidney anatomical and pathological changes when parasitized by Dioctophyme renale. Materials, Methods & Results: The kidneys of 21 dogs diagnosed with dioctophymiasis were nephrectomized, analyzed by ultrasound and forwarded to macro and microscopic analysis. Macroscopically, the kidney size was measured as well as its renal capsule thicknes. The presences of dilatation of the renal pelvis and ureter, as well as changes of the capsule, were also observed. These fragments were collected and submitted for routine analysis and stained with hematoxylin and eosin. Histopathological examination was performed blindly by three evaluators. The intensity of fibrosis was evaluated by the presence or absence of infiltration, the absence or presence of parasite eggs and when present whether there was inflammatory tissue response, among other changes. All received organs were right kidneys and showed clear atrophy or absence of the parenchyma. The kidney size ranged from 3,8x2,5x1,3 cm to 8,4x8,2x4,0 cm and the capsule thickness between 0.1 and 3.6cm. In renal capsule were observed whitish, irregular and firm plates (10 out of 21 cases) and papilliform projections (4 out of 21). In two specimens were identified cases of hydroureter and hydronephrosis. Microscopically, all specimens had some degree of fibrosis which replaced the renal parenchyma, six classified as mild, ten were moderate and five intense. In 13 cases there was intense deposition of parasite eggs and 18 cases showed inflammatory infiltrate of which one was pyogranulomatous and one granulomatous. Papilliform projections were observed in six out of 21 cases (composed of connective tissue proliferation and neovascularization), there was also hyperplasia of the pelvis transition epithelial (6 out of 21) and osseous metaplasia of the renal capsule (4 out of 21). The vessels walls were hypertrophic in nine out of 21 cases. Discussion: The diagnosis of dioctophymiasis was performed by ultrasonography. All 21 kidneys analyzed were rights; this is related to the parasite penetration in the duodenal wall, which tends to migrate by anatomic proximity to the right kidneys. Dioctophyme renale feeds through digestion and ingestion of the renal parenchyma by the action of parasite’s oesophageal enzymes causing progressive destruction of the cortical and medullar layers and consequently the proliferation of fibrous tissue. In this study, different intensities of fibrosis were observed. Bone metaplasia characterizes the chronicity of the process and the connective tissue’s attempt to adapt. Animals affected by dioctophymiasis often develop chronic renal failure. Chronic renal failure is characterized by continuous and irreversible morphologic changes in the renal parenchyma with loss of nephron components and the formation of a vicious cycle of replacement by fibrous connective tissue. The hypertrophy of vascular epithelium observed in six cases of this study may be associated with fibrous connective tissue proliferation stimulus. The injuries described here may be related to the parasitosis late diagnosis.